Urban poverty and social inclusion policies in complex communities (2008)
The methods for the measurement of poverty, inequality and exclusion, allow the understanding of the current social conditions; such conditions characterize the present societies and define the complex communities by the way of expressing the social fragmentation. This fragmentation is demonstrated in the relations of access to goods and services, as in the physical space; the studies have demonstrated that in Latin America the patrimonial component is the one in greater deficiency exceeding food and capacities (health and education). The urban space accentuates the inequalities, generates an impact in the urban life of the social groups. The conditions in the cities of Latin America are deplorable; the uncovered necessities exceed the forecasts and continue increasing. This article analyzes the conditions of the urban poverty in Latin America and the policies adopted to confront the phenomenon of poverty in order to propose guidelines for social inclusion.